Deep Learning in Bioinformatics: Techniques and Applications in Practice - Izadkhah, Habib (Elsevier Science & Technology, 2022)
Deep Learning in Bioinformatics: Techniques and Applications in Practice introduces the topic in an easy-to-understand way, exploring how it can be utilized for addressing important problems in bioinformatics, including drug discovery, de novo molecular design, sequence analysis, protein structure prediction, gene expression regulation, protein.